Distribution and antifungal susceptibility patterns of Candida species at a university hospital in Northern Turkey - Calgin, Mustafa Kerem; Cetinkol, Yeliz (The Journal of Infection in Developing Countries, 2018)
Introduction: The aim of this study was to establish local resistance profiles of Candida species isolated from various clinical specimens by identifying isolates and determining their susceptibilities to commonly used antifungal agents. Methodology: All isolates were identified to species level and amphotericin B, flucytosine, fluconazole, voriconazole, caspofungin and micafungin antifungal susceptibility testing was performed using Vitek 2 Compact Advanced Expert System (AES). Results: The specimens consisted of 152 urines (69%), 49 blood (22%), 15 sputum (7%) and 4 wound (2%) samples. Of the 220 isolated Candida strains, the most prevalent species were Candida albicans (43.3%), Candida tropicalis (25%) and Candida parapsilosis (13.7%). In blood specimens C. parapsilosis was the dominant species (43%), followed by C. albicans (32.5%) and C. tropicalis (12.2%). Overall resistance to amphotericin B, flucytosine, fluconazole, voriconazole, caspofungin and micafungin was 7.3%, 10%, 9.4%, 7.3%, 2% and 6.5%, respectively. Conclusions: Due to the increase in patient populations at risk of Candida infections, rational treatment planning and resistance rates should be checked along with antifungal susceptibility testing on C. albicans, C. tropicalis and C. parapsilosis isolates.